Perbandingan Kinerja Topologi Canonical Dan Folded Clos Tree Pada Jaringan Data Center - Suryayusra; Edi Surya Negara; Maria Ulfa (Institute of Information Technology and Social Science (IITSS), 2020)
A Data Center (DC) can be said to be of quality if it can provide optimal service. Optimal service means that the access provided must be free of distractions. Disturbances can originate from outside the system or from within the system itself Both can only be overcome if a DC has a good architecture. There are two comparable topologies compared, namely canonical tree and folded closs tree topologies which aim to get better data transfer rates between the two and which one has better data transfer speeds between the two when interference occurs. In analyzing these comparisons, the authors compare using the ftp method in mathematically analyzing the data transfer rates of the two DC architectures above using the same comparator data on 3 trials so as to obtain an accurate result, which one has better data transfer speeds and the best data transfer when both are interrupted in case one of the best flow switches is interrupted.